2021
DOI: 10.21067/jrpe.v6i1.5324
|View full text |Cite
|
Sign up to set email alerts
|

Efikasi diri, pendidikan kewirausahaan dan ekspektasi pendapatan : pengaruh terhadap minat berwirausaha

Abstract: ABSTRAK: Penelitian ini membahas tentang Pengaruh Efikasi Diri, Pendidikan Kewirausahaan dan Ekspektasi Pendapatan terhadap Minat Berwirausaha. Populasi dalam penelitian ini adalah mahasiswa Pendidikan Ekonomi Universitas Kanjuruhan Malang sejumlah 55 mahasiswa, Teknik pengambilan sample menggunakan sampel jenuh sejumlah 55 mahasiswa. Jenis penelitian ini adalah penelitian kuantitatif. Metode statisik penelitian ini menggunakan Regresi Linier Berganda dengan prasyarat uji asumsi klasik uji normalitas, uji mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…The first hypothesis in this study was rejected because it was insignificant, this represents that unesa Labschool High School students already understand that high income expectations do not rule out the possibility of a large risk of loss. This is in line with the research results from Satyantoro & Andayani (2021) which suggest that income expectations do not affect the interest in entrepreneurship in its research population due to concerns about fluctuating incomes in a demanding era of all-certainty. Supported by research results from Prayogo (2020); Sintya (2019)which also discuss the variable results of income expectations directly affecting insignificant and positively affecting the interest in entrepreneurship, because not everyone can depend on erratic incomes and very complicated levels of business competition.…”
Section: The Impact Of Income Expectations On Entrepreneurial Interestsupporting
confidence: 87%
See 4 more Smart Citations
“…The first hypothesis in this study was rejected because it was insignificant, this represents that unesa Labschool High School students already understand that high income expectations do not rule out the possibility of a large risk of loss. This is in line with the research results from Satyantoro & Andayani (2021) which suggest that income expectations do not affect the interest in entrepreneurship in its research population due to concerns about fluctuating incomes in a demanding era of all-certainty. Supported by research results from Prayogo (2020); Sintya (2019)which also discuss the variable results of income expectations directly affecting insignificant and positively affecting the interest in entrepreneurship, because not everyone can depend on erratic incomes and very complicated levels of business competition.…”
Section: The Impact Of Income Expectations On Entrepreneurial Interestsupporting
confidence: 87%
“…Subsequent results showed that the income expectation variable had a positive and significant direct impact on the self-efficacy variable with a coefficient path analysis value of 0.289 and a p-value of <0.001. the fourth research hypothesis is "accepted" with results that correspond to the research results of Satyantoro & Andayani (2021); Sintya (2019) states that the income expectations owned by each person will be different because they refer to the skills and knowledge possessed by the person. The higher the confidence in the skills and knowledge possessed, the greater the individual's desire to obtain a high and unlimited income.…”
Section: The Impact Of Income Expectations On Self-efficacymentioning
confidence: 90%
See 3 more Smart Citations